An Analysis of The Village Names in Luang Prabang Municipality: https://doi.org/10.69692/SUJMRD0901243 - Sathamma, Phothong; Bouphapanya, Souliya; Pheuaphom, Singthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purpose of this research is to analyze the structures and meanings relating to village names in LUANG PRABANG municipality. Data is collected from documents and interviews with villages in 64 villages. The results revealed that: The village names could be classified into 2 categories: non-topographical characteristics and topographical characteristics of that there were 35 village names focused on nontopographical characteristics and 29 village names on topographical characteristics. In addition the results found that there were 3 characteristics of words in the village names: Firstly, a single word with two morphemes consisted in 51 village names, a single word with one morpheme is comprised in 7 village names, a single word with three morphemes consisted in 6 village names. Secondly, the compound words of village names are divided into 3 patterns: "Head noun + Modifier" were 52 village names, "Subject + Predicate" were 4 village names, "Verb + Object" were 1 village name. Thirdly, the structure village names are divided into 2 categories: One word was 7 village names, Compound words were 57 village names. Finally, meanings of village names could be categorized into 3 types: The words were having denotation were 58 village names, The words were having connotation were 4 village names, The words were having connotation and denotation were 2 village names.